Knowing Your Pharmacist's Name - Lisa Dragic; Vivan Pham; Albert Wertheimer (University of Minnesota Libraries Publishing, 2015)
Pharmacists are the most accessible health care providers to the general public. Pharmacists are experts in helping patients get the most out of today's complicated medications. Pharmacists ensure safe and effective use of medications. The American Pharmacists Association pitched a campaign, "Know your medicine, know your pharmacist." Before one can know their medicine, one must know their pharmacist. This study was conducted to see whether older or younger and male verse female patients knew their pharmacist's name better in the Philadelphia area, as a pilot study.   Type: Commentary